Constitutional POLE variants causing a phenotype reminiscent of constitutional mismatch repair deficiency. Issue 1 (2nd December 2021) - Sehested, Astrid; Meade, Julia; Scheie, David; Østrup, Olga; Bertelsen, Birgitte; Misiakou, Maria Anna; Sarosiek, Tomasz; Kessler, Elena; Melchior, Linea C.; Munch‐Petersen, Helga Fibiger; Pai, Reetesh K.; Schmuth, Matthias; et al.
Abstract: Heterozygous POLE or POLD1 germline pathogenic variants (PVs) cause polymerase proofreading associated polyposis (PPAP), a constitutional polymerase proofreading deficiency that typically presents with colorectal adenomas and carcinomas in adulthood. Constitutional mismatch‐repair deficiency (CMMRD), caused by germline bi‐allelic PVs affecting one of four MMR genes, results in a high propensity for the hematological, brain, intestinal tract, and other malignancies in childhood. Nonmalignant clinical features, such as skin pigmentation alterations, are found in nearly all CMMRD patients and are important diagnostic markers. Here, we excluded CMMRD in three cancer patients with highly suspect clinical phenotypes but identified in each a constitutional heterozygous POLE PV. These, and two additional POLE PVs identified in published CMMRD‐like patients, have not previously been reported as germline PVs despite all being well‐known somatic mutations in hyper‐mutated tumors. Together, these five cases show that specific POLE PVs may have a stronger "mutator" effect than known PPAP‐associated POLE PVs and may cause a CMMRD‐like phenotype distinct from PPAP. The common underlying mechanism, that is, a constitutional replication error repair defect, and a similar tumor spectrum provide a good rationale for monitoring these patients with a severe constitutional polymerase proofreading deficiency according to protocols proposed for CMMRD. Abstract : Here, we report three cases with a phenotype highly suggestive of constitutional mismatch repair deficiency (CMMRD) caused by heterozygous constitutional POLE pathogenic variants (PVs.) These three, and two additional POLE PVs identified in published CMMRD‐like patients, have not previously been reported as germline PVs despite all being known somatic mutations in hyper‐mutated tumors. Together, these five cases show that that polymerase proofreading deficiency should be considered as a differential diagnosis to CMMRD and suggest that specific POLE PVs associated with an exceptional constitutional penetrance may have a stronger "mutator" effect than known polymerase proofreading associated polyposis‐ (PPAP‐)associated germline POLE PVs.